Efficacy and safety of the biosimilar ABP 215 compared with Bevacizumab in patients with advanced nonsquamous non-small cell lung cancer (MAPLE): a randomized, double-blind, phase III study - Thatcher, Nicholas; Thomas, Michael (Clinical cancer research, 2019)
Purpose: This phase III study compared clinical efficacy and safety of the biosimilar ABP 215 with bevacizumab reference product (RP) in patients with advanced nonsquamous non-small cell lung cancer (NSCLC). - Patients and Methods: Patients were randomized 1:1 to ABP 215 or bevacizumab 15 mg/kg every three weeks for 6 cycles. All patients received carboplatin and paclitaxel every three weeks for ≥4 and ≤6 cycles. The primary efficacy endpoint was risk ratio of objective response rate (ORR); clinical equivalence was confirmed if the 2-sided 90% confidence interval (CI) of the risk ratio was within the margin of 0.67 to 1.5. Secondary endpoints included risk difference of ORR, duration of response (DOR), progression-free survival (PFS), and overall survival (OS); pharmacokinetics, adverse events (AEs), and incidence of antidrug antibodies (ADAs) were monitored. - Results: A total of 820 patients were screened; 642 were randomized to ABP 215 (n = 328) and bevacizumab (n = 314). Overall, 128 (39.0%) and 131 (41.7%) patients in the ABP 215 and bevacizumab groups, respectively, had objective responses [ORR risk ratio: 0.93 (90% CI, 0.80-1.09)]. In the ABP 215 and bevacizumab group, 308 (95.1%) and 289 (93.5%) patients, respectively, had at least 1 AE; 13 (4.0%) and 11 (3.6%) experienced a fatal AE. Anti-VEGF toxicity was low and comparable between treatment groups. At week 19, median trough serum drug concentration was 132 μg/mL (ABP 215 group) and 129 μg/mL (bevacizumab group). No patient tested positive for neutralizing antibodies. - Conclusions: ABP 215 is similar to bevacizumab RP with respect to clinical efficacy, safety, immunogenicity, and pharmacokinetics. The totality of evidence supports clinical equivalence of ABP 215 and bevacizumab.
Gesehen am 30.01.2020